From lost to found: the silent transfer of patients on Antiretroviral Therapy in Khayelitsha, South Africa - Hennessey, Claudine (Department of Public Health and Family Medicine, 2016)
Incorrect classification of silent transfer (STF) patients as lost to follow-up (LTF) negatively impacts accurate assessment of retention in care for antiretroviral (ART) programmes. Understanding reasons why patients STF and what proportion of LTF patients constitute this silent transfer phenomenon is necessary to ensure patient continuity of care. We attempted to identify STF patients using the routine government electronic monitoring systems. Furthermore, we sought to identify potential reasons for the STF phenomenon through patient surveys and healthcare provider interviews, in order to guide policy and improve programmatic outcomes. In this mixed methods approach, we selected patients identified as LTF between 2008-2012 in three health facilities from Khayelitsha, Western Cape. Identified patients were subsequently searched for using a combined provincial patient data set. Once consent was obtained, sampling of patients and healthcare providers, using convenience and snowballing methods respectively, were selected for participation. Ninety percent of patients believe it necessary to inform facility staff of the intent to transfer, 56% of patients interviewed cited fear of negative attitudes from staff regarding transfer request (65%), family situations (30%), and long waiting times (11%) as contributing factors to silently transferring care between facilities. Healthcare providers cited stigma, family obligations and/or support, and migration to the Eastern Cape as main reasons for patients transferring. Healthcare providers cited incomplete or lack of transfer documentation as the biggest barrier to timeous treatment of the transfer patient. Incorrect reporting of patients as lost to follow-up negatively affects the treatment programmes retention in care. Negative staff attitudes and poor operational services prevent patients informing staff of transfer intent. The treatment programme must adapt current transfer policies in order to facilitate the transfer process for all patients, including those experiencing emergencies and life events. Linked electronic patient monitoring systems will improve accurate retention in care reporting and improve fluidity of transferring of patients between health services.